Knowledge and attitude of pediatric dentists, general dentists, postgraduates of pediatric dentistry, and dentists of other specialties toward the endodontic treatment of primary teeth - P Devendra Patil; A Farhin Katge; D Bhavesh Rusawat (Wolters Kluwer Medknow Publications, 2016)
Background: Pediatric dentists (PDs) play an important role in treating primary teeth and oral health care needs for children. Pulp therapy is widely used in the treatment of primary teeth. The choice of endodontic treatment modality changes among general dentist (GD) and PD. Aim and Objectives: The aim of this study is to determine the attitudes of PDs, GDs, postgraduates (PGs) of pediatric dentistry and dentists of other specialties toward endodontic treatment of primary teeth. Materials and Methods: A structured 20-item questionnaire was formulated in English and distributed to PD, GD's, PGs of pediatric dentistry, and dentist of other specialties. The filled questionnaire survey was statistically analyzed using simple descriptive analysis and inferential analysis was performed using Chi-square t- test. Results: Out of the 237 survey respondents, 27.43% were BDS (GD's), 16.88% were MDS (PD), 12.66% were PG's (pediatric dentistry), and 43.04% were MDS (other than PD). About 91.6% of the total respondents preferred endodontic procedures in primary teeth. Conclusion: The study concluded that the GD's, PD's, and dentist of other specialty differ in their treatment recommendations for primary teeth. The GDs and dentist of other specialty were regularly performing pulp therapy in primary teeth and should frequently update their knowledge about endodontic procedures in primary teeth.